2009
DOI: 10.1021/jp906414q
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of the Hydrogen Storage Compound NaMgH3

Abstract: Figure S1: Thermal activation plot of rate ω H of hydrogen motion. The data points are from ω H = 1/T 1D and from linewidth ∆f using eqn. (6), from the circled data points in Fugire 6. The straight line correspond to activation parameters from eqn. (5), ω o = 2x10 14 s -1 and activation energy Ε=95 kJ/mol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…Figure 9 shows the pure frequency dependence of the NMR spectrum rather than the magnetic field effect. Measurement at a higher Larmor frequency pro- The temperature-induced 1 H NMR spectra and the two-component spectra have been observed for MgH 2 [3], LiBH 4 [4], NaMgH 3 [5], NaH [6], and the KH 2 PO 4 family [7,8].…”
Section: Nmr Spectra With Variable Larmor Frequencymentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 9 shows the pure frequency dependence of the NMR spectrum rather than the magnetic field effect. Measurement at a higher Larmor frequency pro- The temperature-induced 1 H NMR spectra and the two-component spectra have been observed for MgH 2 [3], LiBH 4 [4], NaMgH 3 [5], NaH [6], and the KH 2 PO 4 family [7,8].…”
Section: Nmr Spectra With Variable Larmor Frequencymentioning
confidence: 94%
“…Ionic conduction facilitated by lattice defects also causes the narrowing of the NMR spectra [2]. The development of a narrow NMR spectrum superposed with a broad NMR spectrum has been observed for some hydrates [3][4][5][6], hydrogen-bonded compounds [7,8], and nanocrystalline Li compounds [9][10][11]. The broad component is assigned to immobile ions with dipole-dipole couplings on a rigid lattice, while the narrow component is assigned to mobile ions decoupled from the matrix of each material.…”
Section: Introductionmentioning
confidence: 98%
“…10) The NMR spectrum from the composite FID is confirmed to be nearly identical to the magic-echo spectrum for some hydrides, 10) and then the extrapolation procedure has been applied to various hydrogen compounds. [14][15][16][17] In this paper, we adopted a replacement procedure to analyze the proton FID for Mg(OH) 2 and Ca(OH) 2 , which made the FT-NMR analysis better than that in a previous report. 6) The portion of the FID obscured by probe ringing and/or dead time was replaced by the extrapolated data using an analytical fitting function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that NaH hydride addition greatly improves the hydrogen storage properties of MgH 2 because of the formation of NaMgH 3 [ 19 ]. Fast hydrogen mobility in NaMgH 3 has been revealed by H NMR study and related to its perovskite structure [ 20 ]. Therefore, it is believed that, in a mixture of MgH 2 and NaMgH 3 , hydrogen gas adsorption and dissociation are activated by NaMgH 3 grains which offer fast diffusion pathway for hydrogen atoms into MgH 2 [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%